Analysis of bankruptcy threat for risk management purposes: A model approach - Monika Wieczorek-Kosmala; Joanna Błach; Joanna Trzęsiok (International Journal of Financial Studies, 2018)
In previous works, the importance of risk management implementation was addressed with regard to the problem of bankruptcy threat, with the explanation of risk impact on higher bankruptcy costs or the underinvestment problem. However, the evaluation of the impact of risk outcomes is technically linked to risk frequency and risk severity as the two dimensions of the risk map. The purpose of our study is to advocate two additional dimensions that incorporate liquidity and/or debt capacity constraint in the aftermath of risk occurrence. In the conceptual dimension, we propose a model that may support the appropriate design of risk management methods, by scaling a company's ability to self-resist the risk outcomes. The study provides the empirical illustration of the frequency of the distinguished patterns of risk self-resistance. It was found that most frequently companies face the limited ability to self-resist risk outcomes, due to high debt capacity and high liquidity constraints. We also found statistically significant interdependencies between the company's sector and the risk self-resistance. It supports the conclusion that the level of liquidity and debt capacity constraints and thus the ability to retain risk outcomes is sector-specific. It has important implications for the effective design of risk management methods.
Keywords: D81; M21; G32; G33; 330; bankruptcy threat; liquidity constraint; cash holdings; debt capacity constraint; leverage; risk management; risk financing methods